2013
DOI: 10.5194/bg-10-2539-2013
|View full text |Cite
|
Sign up to set email alerts
|

Improved quantification of microbial CH<sub>4</sub> oxidation efficiency in arctic wetland soils using carbon isotope fractionation

Abstract: Abstract. Permafrost-affected tundra soils are significant sources of the climate-relevant trace gas methane (CH4). The observed accelerated warming of the arctic will cause deeper permafrost thawing, followed by increased carbon mineralization and CH4 formation in water-saturated tundra soils, thus creating a positive feedback to climate change. Aerobic CH4 oxidation is regarded as the key process reducing CH4 emissions from wetlands, but quantification of turnover rates has remained difficult so far. The app… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
64
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(75 citation statements)
references
References 74 publications
(81 reference statements)
11
64
0
Order By: Relevance
“…However, the observed concentrations are within the lower range of boreal rivers for which average concentrations between 10 and 1400 nM have been reported (Middelburg et al, 2002). Isotopic data of methane in creek water and in the Olenekskaya Channel (−42 and −39 ‰) showed a rather heavy methane signature when compared to other Arctic lakes (−58 ‰, Walter et al, 2008) and is much more closer to water samples from polygons at near-by Samoylov Station (−45 ‰, Preuss et al, 2013). This unusual signal could indicate that the organic matter used for methane production probably also had a heavy signature.…”
Section: Processes Within the Rivermentioning
confidence: 82%
See 1 more Smart Citation
“…However, the observed concentrations are within the lower range of boreal rivers for which average concentrations between 10 and 1400 nM have been reported (Middelburg et al, 2002). Isotopic data of methane in creek water and in the Olenekskaya Channel (−42 and −39 ‰) showed a rather heavy methane signature when compared to other Arctic lakes (−58 ‰, Walter et al, 2008) and is much more closer to water samples from polygons at near-by Samoylov Station (−45 ‰, Preuss et al, 2013). This unusual signal could indicate that the organic matter used for methane production probably also had a heavy signature.…”
Section: Processes Within the Rivermentioning
confidence: 82%
“…Thus, the methane flux from the Lena River and its various channels is about 3-10 times higher than the terrestrial emissions. One reason for the lower terrestrial emission could be that for the terrestrial environment an intense microbial methane oxidation was observed (Preuss et al, 2013;Liebner and Wagner, 2007), which seems to be absent in the river. However, for an assessment of the regional methane fluxes from the whole Lena Delta, it would be important to take into account the different areas of river channels, thaw ponds and terrestrial environment.…”
Section: Processes Within the Rivermentioning
confidence: 99%
“…Isotopic fractionation factors of methane oxidation (α ox = k 12 k 13 ) were determined as described in Preuss et al (2013), using the isotope fractionation approach (Coleman et al, 1981).…”
Section: Net Methane Oxidation/production and Determination Of Isotopmentioning
confidence: 99%
“…f CH4anox = 0.5. We used this value in the reference simulation because it was previously reported in the literature as characteristic of water-saturated polygon centers (Preuss et al, 2013), and it is similar to the value reported for unsaturated zones in boreal bogs (Wahlen and Reeburgh, 2000). However, in wetland areas, CH 4 is still subject to oxidation after its production and the CO 2 :CH 4 ratio is 890 expected to increase and to vary among types of wetlands (Bridgham et al, 2013).…”
Section: Sensitivity Experimentsmentioning
confidence: 86%